The Effectiveness of Social Media Utilization as a Digital Marketing Tool for Micro, Small, and Medium Enterprises (MSMEs) - Imay Delin Sabtha Dewi; Wahyuni Zahra Hidayah; Putri Ayu Salsabillah (PT. Hidayat Muda Intelektual, 2026)
This study aims to evaluate the effectiveness of social media utilization within digital marketing strategies for Micro, Small, and Medium Enterprises (MSMEs) through a case study approach. The research employs a descriptive qualitative method with data collection techniques including interviews and observations conducted on two MSMEs: Es Cemil Yummy, which actively uses social media, and Pentol Kuah Merapi, which has not yet utilized social media but is located in a strategic area. The findings indicate that the use of social media, particularly Facebook, can enhance business visibility, expand market reach, and drive sales growth. Meanwhile, a strategic business location has been proven to sustain business continuity despite limited market expansion. This study concludes that social media is an effective marketing tool and represents a strategic necessity for MSMEs to develop sustainably in the digital era. The study also recommends that MSMEs which have not yet adopted digitalization should begin integrating social media into their marketing strategies.